The effects of fatigue on decision-making in junior rugby league - Redman, K. (Journal of Australian Strength and Conditioning, 2017)
During the later stages of sporting competition, a decrease in performance is regularly observed and is often attributed to fatigue. Although, it is unclear if the decrement of performance is exclusively due to physiological fatigue or an indicator of a decline in decision-making (DM) performance. Rugby league (RL) is a highly physical and tactical team sport wherein players are required to make decisions under time and fatigued based constraints. The aim of this study was to determine the effects of match-related fatigue on DM in junior RL players. A secondary aim of this study was to compare positional playing groups, forwards and backs, and determine if fatigue differentially effects DM performance